Biosignals-based driver’s awareness/emotion monitoring for future car design - Yao, Xibing (2016)
With the increasing demand for safer and better driving experience, driver assistance systems (DAS) are receiving more and more attention in car industry. By using sensors, there are many biosignals measurements available to recognize driver’s biosignals. With the collected biosignals data, programming can be used to analyze the situation.